Term Khalifah Dalam Al-Qur’an: Analisis Sintagmatik-Paradigmatik Ferdinann De Sausurre - syaifullah syaifullah (Jurnal Ulunnuha, 2021)
This article reinterprets the word caliph with a modern linguistic approach initiated by Ferdinand de Sausurre, namely the syntagmatic-paradigmatic analysis approach.  This paper uses a qualitative method by grouping words and analyzing words in the Qur'an.  In this paper, it is explained that caliph does not have a single and narrow meaning but is a living word when it is related to the lexemes that surround it.  Syntagmatically the caliph has a relationship with the word; Rabb, Angel, qaum and 'ard.  While in a paradigmatic relation with the word; Imam, ulu al-amri, ulul al-bab, ulama', auliya' and humans.